Formação de psicólogos: análise curricular - Calais, Sandra Leal [UNESP]; Pacheco, Elisabeth M. De Camargo (Associação Brasileira de Psicologia Escolar e Educacional (ABRAPEE), 2001)
This research characterized a Psychology study course within a public university, by analyzing official course plans (1999), applicable to discipline and probation programs. The analysis revealed that in 4140 hours, 15.2% are connected domain disciplines, 32.5% basic disciplines, 25.4% specific disciplines, 7.2% pedagogical disciplines and 19.6% supervised probation programs. Within basic single-theory disciplines, over multi-theory disciplines, 44% adopted a behaviorist approach, 19% adopted a psychosocial approach, 12.5% adopted an ethnological approach, 12.5% adopted a biological approach, 6% adopted a Piagetian approach and 6% adopted the vital cycle theory; therefore the multi-theoretical approach would be the wiser choice. Almost all disciplines of the connected domain type had psychology-related contents, which suggests the studies concern with the interrelation of the various disciplines. As far as the probation programs are concerned, the predominance of uni-theoretical approach suggests coherence in the advanced years of the studies.

Objetivou-se caracterizar um curso de Psicologia de IES pública, São Paulo, analisando planos oficiais de ensino (1999) de suas disciplinas e estágios. Análises curriculares revelaram que, de 4140 horas, 15,2% são de disciplinas de domínio conexo, 32,5% básicas, 25,4% específicas, 7,2% pedagógicas e 19,6% de estágios supervisionados. Houve predominância do enfoque uniteórico. Nas disciplinas básicas uniteóricas 44% tinham abordagem behaviorista, 19% psicossocial, 12,5% etológica, 12,5% biológica, 6% piagetiana e 6% teoria do ciclo vital; o ideal seria o enfoque multiteórico ou o equilíbrio. A maioria das disciplinas de domínio conexo tinha conteúdo relacionado à Psicologia, sugerindo preocupação do curso com a inter-relação. Nos estágios supervisionados, o predomínio do enfoque uniteórico mostra coerência na organização dos conteúdos de final de curso.
Psychologist´s graduation: an analysis of the curriculum
Keywords: Psychologist formation; Curriculum analysis; Psychology; Formação do psicólogo; Análise curricular; Psicologia